PENGARUH PEMBERIAN LABU SIAM TERHADAP PENURUNAN TEKANAN DARAH - Sitepu, Marlen Sadrina; Sihaloho, Wilfa Muslimah; Krisna, Putri; insani, Septa dwi; Sitorus, Husna Sari (INSTITUT KESEHATAN DELI HUSADA, 2024)
Hyepertension in Indonesia is caused by a lifestyle that consumes foods with higt cholesterol levels, foods with higt salt content, lack of exercise and cannot be separated from genetic factors. Elderly is a period where individuals have entered a period of physical decline which is characterized by wrinkled skin, gray hair, missing teeth, hearing loss, blurred vision, and excessive body proportions, so that it is said that elderly are individuals in this age group who have entered a period of physical decline final stage of their life.